An Introduction to Impossible Futures and the Ethics of Hopelessness - Udoewa, Victor (Futures Reframed, 2026)
We live in a world of many worlds—the pluriverse. In each world, concepts and ideas have different experiences and definitions, including futures, possibility, and hope. In a Eurocentric, Western world, design and futures practices are built on the ethics of hope, agency, and possibility. However, there are other worlds with different realities. We introduce you to the world of Black Liberation, an existence caught between the now and not yet. For many Afro-descendant people, their reality does not include hope. Their world is full of hopelessness. This pluriversal understanding explains why many White futures methods and practices do not work for underutilized communities, especially communities of oppressed peoples. White futurists often create futures that community members do not want or own.Paradoxically, in the community of hopelessness, Afro-descendant people have found an ethic with which they still move forward, not based on hope in possibility but on hopelessness in impossibility. This hopeless, impossible futures practice is infused with a blues sensibility, a jazz spirituality, and a spirituals rituality. Impossibility and hopelessness are not euphemisms, fleeting states, or conditions of inadequate vision. We truly mean impossible, hopeless. Impossible futures is an inclusive practice which specifically uses an ethics of hopelessness. With an ethic of hopelessness all community members—the hopeful, the hope indifferent, the hopeless—are invited in and can flourish together without hope of achieving impossible futures, yet moving toward them. Rather than a goal to be achieved, Black liberation, based on the ethics of hopelessness, is a way of being, being regardless of hope.